STUDY ON UTILIZATION OF FLY ASH AS COVER LAYERING MATERIAL IN PREVENTING THE FORMATION OF ACID MINE DRAINAGE IN COAL MINE - Lianti Anastasya, Caroline
One of the methods used to prevent acid mine drainage is encapsulation. The encapsulation method is a method that places PAF (Potentially Acid Forming) rocks under NAF (Non Acid Forming) or acid consuming material in such a way as to minimize the meeting of sulfide minerals with air and water. In this study, it utilized fly ash from the PT Bukit Energi Servis Terpadu power plant in the Banko Barat mining area, Tanjung Enim as an alternative layering material to replace NAF. To determine the possibility of using fly ash as a layering material, physical characterization tests, and geochemical characteristics of fly ash and PAF materials were carried out, as well as column leaching tests with several layering simulation scenarios. The layering simulation scenario is carried out by varying the amount of fly ash as a layering material.